Modelo de negócio para o comercializador de energia com a liberalização do mercado de eletricidade residencial do Brasil - Thomasi, Virginia (2025)
The energy market liberalization for residential consumers has been adopted in several countries to promote benefits. However, conducting an in-depth debate on these benefits and carefully implementing a transition plan when opening this market to residential consumers is essential. In residential electricity retail markets, competition tends to grow gradually, with delays in removing barriers for new participants, which can be considered a policy failure that harms energy retailers and potential consumers. In this context, innovation in the business model becomes essential to overcome the challenges faced by the sector. This thesis focuses on the case study of Brazil, where the gradual opening of the electricity market is scheduled to include the residential class from 2028. The residential class comprises most consumer units, representing 78 million units, equivalent to 86.5% of the total. This thesis aims to assist the Brazilian electricity sector in migrating residential consumers to the free energy market through a business model targeted at retail marketers in the residential energy market. To achieve this goal, the study was divided into two phases: an analysis of the scenario in different countries and modeling for the construction of the business model. In the first phase, a systematic review of the literature and an analysis of gray literature related to the opening of the residential market were conducted. This review identified 16 barriers to market success, 17 enhancements needed for market consolidation in any country, and 10 opportunities for energy market stakeholders with the opening to residential consumers. In addition, interviews were conducted with 40 industry experts, including members of associations, companies, or agencies linked to the Ministry of Mines and Energy, consulting firms, electrical system installation companies, researchers, and electricity generation, transmission, and/or distribution concessionaires. The second phase began with an exploratory study of the services offered to residential consumers in countries with an open market. Following this, a user experience was conducted for each service, enabling a detailed analysis of the consultation mechanisms. Subsequently, a second systematic literature review was conducted to investigate business models in the energy sector, identifying and categorizing 17 models in product and service and identifying each model's constituent elements. These analyses enabled the development of the business model for retail marketers, establishing a new commercial arrangement aimed at meeting the specific demands of the residential energy market, benefiting sector agents and policymakers.